Influence of fibre dispersion on compression strength of banana fibres reinforced concrete. (March 2016) - Mukhopadhyay, Samrat; Bhattacharjee, Bishwajit
Concretes have a high rate of propagation of cracks. In order to decrease the rate of crack propagation banana fibres have been reinforced in concrete. Banana fibres offer a relatively high surface area for bonding with concrete matrix. The proportion of fibres which have to be reinforced inside the concrete has been optimised to maximise compressive strength. Fibres have been coated with a softening agent to facilitate dispersion and reduce variability of test results.